Financial Stability Is Easier to Green Than Monetary Policy - Christian Pfister; Natacha Valla (Intereconomics)
Abstract In the face of mounting evidence of global warming, which is an irreversible process, central banks, as other policymakers, have to play their part. They need to consider climate risks not only in their internal management, but also when they devise their strategies, conduct their policies and implement their decisions. This article examines the possible impacts of climate risks on the two main variables of interest for monetary policy, economic growth and inflationary pressures. On that basis, it infers the potential consequences for the objective of monetary policy, its conduct and its implementation.